1974
DOI: 10.1590/s0074-02761974000200013
|View full text |Cite
|
Sign up to set email alerts
|

Transferência do Hepatozoon tupinambis, parasita do lagarto Tupinambis teguixin, para a serpente cascavel (Crotalus durissus terrificus), por intermédio do mosquito Culex fatigans

Abstract: Os autores obtiveram a transferência do Hepatozoon tupinambis (Laveran e Salibeni, 1909) parasita do lagarto Teiidae, Tupinambis teguixin, L., para a serpente cascavel, Crotalus durissus terrificus (Laur.), alimentando-a com mosquitos experimentalmente infectados. o parasita mantém os seus caracteres morfológicos no animal receptor, nos limites do tempo observado (cerca de 100 dias). O ofídio receptor apresentou cistos esquizogônicos do fígado.
The authors achieved a transfer of the Hepatozoon tupinambis (L…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

1984
1984
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…Although several authors have been successful in experimentally infecting mosquitoes (Pessoa et al 1974;Wozniak and Telford 1991;Sloboda et al 2007;Telford 2010), the results obtained in the present study suggest that mosquitoes are not the natural hosts of these protozoans of Fig. 2 Sporogonic development of Hepatozoon sp.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Although several authors have been successful in experimentally infecting mosquitoes (Pessoa et al 1974;Wozniak and Telford 1991;Sloboda et al 2007;Telford 2010), the results obtained in the present study suggest that mosquitoes are not the natural hosts of these protozoans of Fig. 2 Sporogonic development of Hepatozoon sp.…”
Section: Discussionmentioning
confidence: 58%
“…Mosquitoes have been used as experimental vectors for Hepatozoon spp. of snakes with success (Pessoa et al 1974;Sloboda et al 2007;Telford et al 2008Telford et al , 2010. Bashtar et al (1991) monitored the developmental stages of Hepatozoon melhorni sp.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, spillover of Hepatozoon spp. in atypical hosts may lead to infections more virulent than those observed in natural hosts [ 196 198 ].…”
Section: Methodsmentioning
confidence: 99%
“…Besides, the gamonts of a same species of Hepatozoon can present slight morphologic changes depending on the host. Pessoa et al (1974) demonstrated that it was possible to transfer H. tupinambis of the lizard Tupinambis teguixin to the snake C. durissus terrificus. The transfer induced changes in the parasite so that in the lizard, Hepatozoon species produced eryth-…”
Section: Boa Constrictor Amaralimentioning
confidence: 99%